Teaching good Excel design and skills: A three spreadsheet assignment project. (June 2017) - Frownfelter- Lohrke, Cynthia
Highlights: Focuses on spreadsheet design which has been shown to reduce errors. Provides an iterative and repetitive approach to teaching spreadsheet design. Uses three Excel assignments to teach spreadsheet design with minimal class time. Requires students to adapt a fundamental design using analytical thinking. Abstract: Over sixty percent of AIS courses cover Excel because it is an important tool for accounting students to learn and master. Although spreadsheet programs like Excel provide powerful analytical tools for business, in practice, they are often created and used by people with minimal programming experience. Consequently, users can often develop spreadsheets containing critical errors, which, in turn, can cause significant losses for their businesses. Errors can be reduced, however, by learning and employing good spreadsheet design techniques. Good spreadsheet design also makes it easier to update and continue to use a spreadsheet over time. This paper describes a method for teaching spreadsheet design where students complete three spreadsheet assignments in an iterative and repetitive process. By the time students have completed these assignments, they will have acquired good spreadsheet design skills and improved their basic Excel skills.